THE IMPACT OF COVID-19 RESTRICTIVE MEASURES ON PHYSICAL ACTIVITY AND SEDENTARY BEHAVIOR IN CHILDREN AND ADOLESCENTS: A SYSTEMATIC REVIEW (Kinesiology, 2022)
The purpose of this review was to gather studies that reported the impact of COVID-19 restrictive measures on physical activity and sedentary behavior in children and adolescents, and to present key findings. The search for articles was performed in three databases of scientific literature: PubMed, Scopus, and Web of Science. We included articles that reported a change in the amount of physical activity and/or sedentary behavior during COVID-19 restrictive measures compared to the period before restrictive measures. The quality of the articles was assessed using the Newcastle-Ottawa Scale. The search returned 1391 hits, of which 23 articles were included in the review. The studies showed that participation in physical activity predominantly decreased (in 17/23 studies) and sedentary behavior predominantly increased (in 16/17 studies). The results regarding the reduction of physical activity were the most consistent for moderate to vigorous physical activity, while the direction of change was mixed for some types of physical activity (e.g., exercise, walking). The results regarding sedentary behavior were mostly consistent in terms of increasing the total amount of sedentary behavior as well as types of sedentary behavior (e.g., watching TV, using tablets). This review showed that COVID-19 restrictive measures have further increased the issue of insufficient physical activity and excessive sedentary behavior among children and adolescents. There is a need for the development of interventions for maintaining/increasing physical activity among children and adolescents that would be suitable for implementation during the future pandemics and other similar crisis situations.